Study of the Effect of Sulfamic Acid on Formation Cu-Se Compounds by CV and EQCM - Hop, Dang Thi Bich; Quang, Pham Hong; Anh, Do Thi Kim; Quan, Do Phuc (VNU Journal of Science: Mathematics - Physics; Vol 30 No 2, 2014)
Abstract: A combination of Cyclic Voltammetry (CV) and Electrochemical Quartz Crystal Microbalance (EQCM) has been used to study the effect of sulfamic acid as a complexing agent on the formation of Cu-Se compounds. It has been found that sulfamic acid does not affect the deposition of Cu in the absent of Se. However, when Cu and Se are simultaneously, sulfamic acid was found to affect strongly the formation of Cu-Se compounds, namely it causes and facilitates the reactions forming Cu-Se compounds. Furthermore, at high concentration, sulfamic acid causes a mass-loss process, leading to a change of composition and a poor surface morphology. A suitable concentration of sulfamic acid can be concerned from these studies. Keywords: Cyclic voltammetry, EQCM, Cu-Se compounds, electrodeposition, thin films.